2022
DOI: 10.3389/fphar.2022.818952
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabonomics Reveals Key Metabolites in Different Types of Childhood Short Stature

Abstract: Nowadays, short stature (SS) in childhood is a common condition encountered by pediatricians, with an increase in not just a few families. Various studies related to the variations in key metabolites and their biological mechanisms that lead to SS have increased our understanding of the pathophysiology of the disease. However, little is known about the role of metabolite variation in different types of childhood SS that influence these biological processes and whether the understanding of the key metabolites f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Our previous study based on nuclear magnetic resonance (NMR) metabolomics found that disturbed glucose metabolism and metabolism and biosynthesis of amino acids were typical metabolic features of SS caused by GHD [10]. A study on 31 children with GHD and 29 children with ISS by ultra-high-performance liquid chromatography-quadrupole/time of flight mass spectrometry (UHPLC-QTOF-MS)-based serum metabolomics found that purine metabolism, the sphingolipid signaling pathway, and sphingolipid metabolism were significantly enriched in childhood SS [11]. However, most of these studies focused on SS in preadolescents, and the metabolic information of adolescent SS was lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study based on nuclear magnetic resonance (NMR) metabolomics found that disturbed glucose metabolism and metabolism and biosynthesis of amino acids were typical metabolic features of SS caused by GHD [10]. A study on 31 children with GHD and 29 children with ISS by ultra-high-performance liquid chromatography-quadrupole/time of flight mass spectrometry (UHPLC-QTOF-MS)-based serum metabolomics found that purine metabolism, the sphingolipid signaling pathway, and sphingolipid metabolism were significantly enriched in childhood SS [11]. However, most of these studies focused on SS in preadolescents, and the metabolic information of adolescent SS was lacking.…”
Section: Introductionmentioning
confidence: 99%